2008
DOI: 10.1080/09286580802105814
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Retinitis Pigmentosa in South Indian Population Aged Above 40 Years

Abstract: Prevalence of RP in South India appears to be alarmingly higher in comparison to those seen in other parts of the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 20 publications
1
43
2
Order By: Relevance
“…The incidence of retinitis pigmentosa is reported to be 0.25:1,000 individuals. One can calculate a relative prevalance for antimalarial retinal toxicity at about 0.025:100,000 35. Based on the variable incidence and prevalence data for the collagen vascular disorders in the literature, it is difficult to calculate the exact risk to patients with rheumatoid arthritis and SLE treated with antimalarials, but from our data it appears that less than 1% of the patients treated with antimalarials are at risk to develop retinal toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…The incidence of retinitis pigmentosa is reported to be 0.25:1,000 individuals. One can calculate a relative prevalance for antimalarial retinal toxicity at about 0.025:100,000 35. Based on the variable incidence and prevalence data for the collagen vascular disorders in the literature, it is difficult to calculate the exact risk to patients with rheumatoid arthritis and SLE treated with antimalarials, but from our data it appears that less than 1% of the patients treated with antimalarials are at risk to develop retinal toxicity.…”
Section: Discussionmentioning
confidence: 91%
“…In these studies, higher prevalence (1/930-1/1,000) (17, 18) of RP and less proportion of autosomal dominant RP (11-15.4%) (15, 16) were noticed compared to the western populations. In Korea, however, there have been a very few reports regarding only clinical features, which were investigated with a small number of RP patients (19-21).…”
Section: Introductionmentioning
confidence: 84%
“…In Asian populations, a few studies of RP from China, Japan and India have presented the prevalence, the clinical features and the inheritance patterns (15-18). In these studies, higher prevalence (1/930-1/1,000) (17, 18) of RP and less proportion of autosomal dominant RP (11-15.4%) (15, 16) were noticed compared to the western populations.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of visual field criteria and ophthalmoscopic fundus appearance, the prevalence of RP in adult population (aged 30 yr) of rural Central India was estimated at 1:750 (Nangia et al 2012). High prevalence of 1:930 and 1:372 was reported in the urban and rural South Indian population aged above 40 yr (Sen et al 2008). The Beijing Eye Study reported RP in about one in 1000 elderly Chinese (aged 40 yr) in North China (Jonas et al 2009), whereas the Beijing Eye Public Health Care Project, a population-based study designed to screen all inhabitants aged of 55 to 85 yr and living in the rural regions of the Beijing municipality, reported prevalence of RP of about 1:4000 (You et al 2013).…”
Section: Clinical Characteristics Of Rpmentioning
confidence: 99%